Discriminating Complainers and Non-Complainers: A Study within the Malaysian Context (Malaysian Management Journal, 2004)
The purpose of this study is to examine whether consumers’ complaint behavior varies according to demographics, psychographics, and attitude toward businesses as well as product attributes. Discriminant analysis on a sample of 122 consumers residing in north Malaysia showed that complainers were males, married, better educated, and holding white collar jobs. Complainers were found to be more confident, more assertive, individualistic, and possessed a positive attitude toward complaining. Consumers who have a more positive attitude towards businesses and product attributes were more likely to complain. The discriminant model was able to predict behavior of complainers better than chance. Implications and suggestions for future research are discussed.